Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
1: 7/20-|x+2/5|=10/21
=>|x+2/5|=-53/420(vô lý)
2: \(\left|\dfrac{3}{7}-x\right|-\left(-\dfrac{2}{3}\right)=1+\dfrac{1}{2}\)
\(\Leftrightarrow\left|x-\dfrac{3}{7}\right|=\dfrac{3}{2}-\dfrac{2}{3}=\dfrac{5}{6}\)
=>x-3/7=5/6 hoặc x-3/7=-5/6
=>x=53/42 hoặc x=-17/42
1/ \(\frac{1}{3x}:\frac{2}{3}=1\)
<=> \(\frac{3}{3×2×x}=\:1\)
<=> \(\frac{1}{2x}=1\)<=> x = \(\frac{1}{2}\)
a, \(\left(3x-5\right)\left(x+1\right)-\left(3x-1\right)\left(x+1\right)=x-4\)
\(\Leftrightarrow\left(x+1\right)\left(3x-5-3x+1\right)=x-4\Leftrightarrow-4\left(x+1\right)=x-4\)
\(\Leftrightarrow-4x-4=x-4\Leftrightarrow-4x-x=0\Leftrightarrow x=0\)
b, \(\left(x-2\right)\left(x+3\right)-\left(x+4\right)\left(x-7\right)=5-x\)
\(\Leftrightarrow x^2+x-6-x^2-3x+28=5-x\Leftrightarrow-2x+22=5-x\Leftrightarrow x=17\)
c, thiếu đề
d, \(3\left(x-7\right)\left(x+7\right)-\left(x-1\right)\left(3x+2\right)=13\)
\(\Leftrightarrow3x^2-147-3x^2+x+2=13\Leftrightarrow x=11+147=158\)
a.\(3x^2-2x-5-\left(3x^2+2x-1\right)=x-4\)
\(\Leftrightarrow-5x=0\Leftrightarrow x=0\)
b.\(x^2+x-6-\left(x^2-3x-28\right)=5-x\)
\(\Leftrightarrow5x=-17\Leftrightarrow x=-\frac{17}{5}\)
c.\(5\left(x^2-10x+21\right)-\left(5x^2-9x-2\right)=0\)
\(\Leftrightarrow-41x+107=0\Leftrightarrow x=\frac{107}{41}\)
d.\(3\left(x^2-49\right)-\left(3x^2-x-2\right)=13\Leftrightarrow x=158\)
Bài 1:
a; \(\dfrac{7}{8}\) + \(x\) = \(\dfrac{4}{7}\)
\(x\) = \(\dfrac{4}{7}\) - \(\dfrac{7}{8}\)
\(x\) = \(\dfrac{32}{56}\) - \(\dfrac{49}{56}\)
\(x=-\) \(\dfrac{49}{56}\)
Vậy \(x=-\dfrac{49}{56}\)
b; 6 - \(x\) = - \(\dfrac{3}{4}\)
\(x\) = 6 + \(\dfrac{3}{4}\)
\(x\) = \(\dfrac{24}{4}+\dfrac{3}{4}\)
\(x=\dfrac{27}{4}\)
Vậy \(x=\dfrac{27}{4}\)
c; \(\dfrac{1}{-5}\) + \(x\) = \(\dfrac{3}{4}\)
\(x\) = \(\dfrac{3}{4}\) + \(\dfrac{1}{5}\)
\(x=\dfrac{15}{20}\) + \(\dfrac{4}{20}\)
\(x=\dfrac{19}{20}\)
Vậy \(x=\dfrac{19}{20}\)
Bài 1:
d; - 6 - \(x\) = - \(\dfrac{3}{5}\)
\(x\) = - 6 + \(\dfrac{3}{5}\)
\(x=-\dfrac{30}{5}\) + \(\dfrac{3}{5}\)
\(x=-\dfrac{27}{5}\)
Vậy \(x=-\dfrac{27}{5}\)
e; - \(\dfrac{2}{6}\) + \(x\) = \(\dfrac{5}{7}\)
\(x\) = \(\dfrac{5}{7}\) + \(\dfrac{2}{6}\)
\(x\) = \(\dfrac{15}{21}\) + \(\dfrac{1}{3}\)
\(x=\dfrac{15}{21}\) + \(\dfrac{7}{21}\)
\(x=\dfrac{22}{21}\)
Vậy \(x=\dfrac{22}{21}\)
f; - 8 - \(x\) = - \(\dfrac{5}{3}\)
\(x\) = \(-\dfrac{5}{3}\) + 8
\(x\) = \(\dfrac{-5}{3}\) + \(\dfrac{24}{3}\)
\(x\) = \(\dfrac{-19}{3}\)
Vậy \(x=-\dfrac{19}{3}\)
1) <=>\(\left[\begin{array}{nghiempt}7-x=5x+1\\7-x=-5x-1\end{array}\right.\)
<=> \(\left[\begin{array}{nghiempt}x=\frac{4}{3}\\x=-2\end{array}\right.\)
2)<=>\(\left[\begin{array}{nghiempt}x+1=3x+2\\x+1=-3x-2\end{array}\right.\)
<=> \(\left[\begin{array}{nghiempt}x=-\frac{3}{2}\\x=-\frac{1}{4}\end{array}\right.\)
3)<=> \(\left[\begin{array}{nghiempt}x+15=3x-1\\x+15=1-3x\end{array}\right.\)
<=>\(\left[\begin{array}{nghiempt}x=8\\x=-\frac{7}{2}\end{array}\right.\)
4) \(\left[\begin{array}{nghiempt}x+7=x+7\\x+7=-x-7\end{array}\right.\)=> \(\left[\begin{array}{nghiempt}x\in R\\x=0\end{array}\right.\)
=> S=R
\(a,\left(\frac{3}{8}+-\frac{3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\left(-\frac{3}{8}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\frac{5}{24}:\frac{5}{6}+\frac{1}{2}\)
= \(\frac{1}{4}+\frac{1}{2}\)
= \(\frac{3}{4}\)
b)\(-\frac{7}{3}.\frac{5}{9}+\frac{4}{9}.\left(-\frac{3}{7}\right)+\frac{17}{7}\)
=\(-\frac{35}{27}+\left(-\frac{4}{21}\right)+\frac{17}{7}\)
= \(-\frac{35}{27}+\frac{47}{21}\)
= \(\frac{178}{189}\)
c) \(\frac{117}{13}-\left(\frac{2}{5}+\frac{57}{13}\right)\)
= \(\frac{117}{13}-\frac{311}{65}\)
= \(\frac{274}{65}\)
d) \(\frac{2}{3}-0,25:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{4}:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{3}+\frac{5}{2}\)
= \(\frac{1}{3}+\frac{5}{2}\)
= \(\frac{17}{6}\)
1) \(\frac{17}{6}-\left(x-\frac{7}{6}\right)=\frac{7}{4}\)
\(\Rightarrow x-\frac{7}{6}=\frac{17}{6}-\frac{7}{4}\)
\(\Rightarrow x=\frac{13}{12}+\frac{7}{6}=\frac{9}{4}\)
2) \(\frac{3}{35}-\left(\frac{3}{5}-x\right)=\frac{2}{7}\)
\(\Rightarrow\)\(\frac{3}{5}-x=\frac{3}{35}-\frac{2}{7}=-\frac{1}{5}\)
\(\Rightarrow x=\frac{3}{5}-\left(-\frac{1}{5}\right)=\frac{4}{5}\)
3) 4) Hjhj^_^^_^
\(\frac{3}{7}x-\frac{1}{2}=\frac{1}{7}\)
\(\frac{3}{7}x=\frac{1}{7}+\frac{1}{2}\)
\(\frac{3}{7}x=\frac{9}{14}\)
\(x=\frac{3}{2}\)
\(\frac{3}{7}.x-\frac{1}{2}=\frac{1}{7}\)
\(\frac{3}{7}.x=\frac{1}{7}+\frac{1}{2}\)
\(\frac{3}{7}.x=\frac{9}{14}\)
\(x=\frac{9}{14}:\frac{3}{7}\)
\(x=\frac{3}{2}\)
vậy \(x=\frac{3}{2}\)